Effectiveness and safety of Rituximab in multiple sclerosis: an observational study from Southern Switzerland - Scotti, Barbara; Disanto, Giulio; Sacco, Rosaria; Guigli, Marilu’; Zecca, Chiara; Gobbi, Claudio (PloS one, 2018)
Despite positive results from phase II and observational studies, Rituximab (RTX) is not currently approved for multiple sclerosis (MS) treatment and can only be used off-label. To characterize MS patients treated with RTX and investigate its effectiveness and safety in a clinical practice setting. Observational analysis of data collected from MS patients at the Neurocenter of Southern Switzerland. Relapses, EDSS worsening, MRI lesion accrual and "evidence of disease activity" (EDA) status were described by Cox regression. RTX and natalizumab treated patients were matched by propensity scores. Out of 453 MS patients, 82 were treated with RTX, 43 (52.4%) relapsing-remitting (RRMS) and 39 (47.6%) progressive MS (median age = 48 [40-54] years, females n = 60 [73.2%], EDSS = 4.0 [2.5-6.0], median follow-up = 1.5 [1.0-2.5] years). Three relapses occurred and 59 (75.6%) patients had not EDA at follow-up end. Time to EDA was similar in RTX and natalizumab treated RRMS patients (HR = 1.64, 95%CI = 0.46-5.85, p = 0.44). Twenty-four patients presented non infusion related adverse events (infections), requiring RTX discontinuation in 6 individuals. These results provide further evidence for RTX being effective in MS treatment, to a similar extent to natalizumab in RRMS. Clinicians must be vigilant for the potential occurrence of infections.